Trombosis venosa cerebral puerperal: implicaciones neurocríticas de un caso clínico - Omar Mendoza; Vanessa Campozano; Ralph Naranjo; Xavier Montenegro; Oswaldo Bolaños (Critical Care & Emergency Medicine, 2026)
Background: Cerebral venous thrombosis (CVT) is an uncommon cerebrovascular emergency with heterogeneous clinical expression. During pregnancy and the puerperium, early recognition is challenging because neurologic symptoms overlap with obstetric and neurocritical differential diagnoses. Case presentation: We report a 30-year-old woman in the immediate puerperium after emergency cesarean delivery complicated by placenta accreta, hypovolemic shock and hysterectomy, who developed akinetic mutism and bilateral brachial paresis during intensive care unit hospitalization. Brain computed tomography, magnetic resonance imaging and venous magnetic resonance angiography demonstrated bilateral frontoparietal cortico-subcortical lesions consistent with venous infarction and involvement of cortical venous branches. Intervention and outcome: Neurocritical support, electroencephalographic evaluation and anticoagulation were implemented, initially with enoxaparin and subsequently with apixaban after individualized thrombotic and hemorrhagic risk assessment. The patient improved progressively, reaching Glasgow Coma Scale 13/15 at discharge and complete functional recovery at follow-up. Conclusion: Puerperal CVT should be suspected in critically ill postpartum patients with unexplained neurologic deterioration. Early neuroimaging confirmation and multidisciplinary management may be associated with favorable neurologic outcome.